2002
DOI: 10.1080/030097402760375223
|View full text |Cite
|
Sign up to set email alerts
|

Six- and 24-month follow-up of pool exercise therapy and education for patients with fibromyalgia

Abstract: Improvements in symptom severity, physical function and social function were still found six and 24 months after the completed treatment programme.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
73
1
11

Year Published

2002
2002
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(90 citation statements)
references
References 25 publications
5
73
1
11
Order By: Relevance
“…At baseline, the participants' score of the EQ-5D utility (mean Ϯ SD 0.31 Ϯ 0.30) matched the scores previously reported to depict patients with fibromyalgia (0.31 Ϯ 0.31) (47). The perceived pain of FM participants (mean Ϯ SD 63 Ϯ 26 mm) was not different from that previously reported for the exercisers with FM at baseline (19,34,43,44). However, Mannerkorpi et al (44) depicted slightly higher levels of pain at baseline (mean Ϯ SD 78 Ϯ 19).…”
supporting
confidence: 63%
See 1 more Smart Citation
“…At baseline, the participants' score of the EQ-5D utility (mean Ϯ SD 0.31 Ϯ 0.30) matched the scores previously reported to depict patients with fibromyalgia (0.31 Ϯ 0.31) (47). The perceived pain of FM participants (mean Ϯ SD 63 Ϯ 26 mm) was not different from that previously reported for the exercisers with FM at baseline (19,34,43,44). However, Mannerkorpi et al (44) depicted slightly higher levels of pain at baseline (mean Ϯ SD 78 Ϯ 19).…”
supporting
confidence: 63%
“…The perceived pain of FM participants (mean Ϯ SD 63 Ϯ 26 mm) was not different from that previously reported for the exercisers with FM at baseline (19,34,43,44). However, Mannerkorpi et al (44) depicted slightly higher levels of pain at baseline (mean Ϯ SD 78 Ϯ 19). The maximal torque of participants (mean Ϯ SD 1.1 Ϯ 0.4 N⅐m/kg) was not significantly different from that previously reported in patients with FM (1.3 Ϯ 0.4) (1); however, they reflected an especially unfit sample of patients with FM who presented with a high number of tender points (mean Ϯ SD 17.2 Ϯ 1.3).…”
mentioning
confidence: 52%
“…Además, existe una necesidad urgente por delinear mejor las características de los pacientes y de los tratamientos para que sea posible la creación de subgrupos de pacientes que respondan mejor a tratamientos específi cos. Varios estudios en FM han sugerido que las limitaciones en los resultados de tratamiento se deben en gran parte a notables diferencias individuales en la respuesta al tratamiento. Aparentemente, no todos los pacientes mostrarán los mismos resultados ante los mismos tratamientos, y esta disparidad parece estar relacionada con la heterogeneidad de la enfermedad y la variabilidad entre pacientes (Goldenberg et al, 2004;Mannerkorpi et al, 2000). Por ponente.…”
Section: Discussionunclassified
“…Dos señalaron que potenciar la condición física mejoraba la incapacidad (Gowans et al, 1999;Mannerkorpi et al, 2000). Sólo un estudio informó de mejoras también en dolor y estado anímico (Cedraschi et al, 2004).…”
Section: Programas De Ejercicio Físicounclassified
“…Jentoft et al [61] detected reductions in pain after 2 sessions per week in a heated pool for 20 weeks, while Gusi et al [62] found that three sessions per week in warm water decreased pain measured on VAS (29%) and pain/discomfort item of the EQ-5D (16%). Mannerkorpi et al [63] achieved a 15% reduction in pain with one pool-based session per week over a 6 month period. WBV is a new therapeutic approach and to our knowledge the study by Alentorn-Geli et al [12] is the only one study to investigate the effect of WBV on FM-related pain; these authors propose exercise plus supplementary vertical WBV as an effective approach for improving pain in FM.…”
Section: Discussionmentioning
confidence: 99%